Photoelectrochemical reduction of p-bromonitrobenzene: Mechanistic discrimination via channel microband array voltammetry - Cooper, J; Compton, R (1998)
Two dimensional voltammetry using an array of channel microband electrodes varying in size from ca. 2 mm to under 1 micron in length, has been used to study the photoreduction of p-bromonitrobenzene. In the dark p-bromonitrobenzene is reduced al - 1.09 V (vs. SCE). On irradiation with strong white light significant photocurrents flowed which were recorded at flow rates from 2 x 10-3 cm3 s-1 to ca. 0.3 cm3 s-1 at various electrode sizes. Mechanistic analysis of these steady-state measurements is shown to unambiguously rule out an ECEE mechanism but suggests instead that an ECE description is the correct one. The analysis is carried out using a WWW based data analysis centre which uses stored working curves to provide best-tit values for the rate constant of the chemical step and for the mean diffusion coefficient of the species involved.